The effectiveness of resource-saving techniques for the cultivation of onions during irrigation in the conditions of the Lower Volga - E. V. Kalmykova; A. A. Novikov; N. Yu. Petrov; O. V. Kalmykova (Овощи России)
Relevance. The main areas under vegetables, including onions, are located in the south of Russia. Inclusion of vegetables in the list of food safety products with a threshold value of 90% will significantly increase the responsibility of agricultural workers at all levels for the production and sale of vegetable products. The purpose of the research is to justify the feasibility and effectiveness of cultivating promising varieties and hybrids of onions during irrigation in the Lower Volga region to obtain yields of 150 or more t/ha of high-quality products.Methods. For the first time in the area of chestnut soils, comprehensive scientific research was conducted on resource-saving techniques to increase the productivity of a vegetable crop in an extremely arid climate by regulating the physiological and biological processes during drip irrigation, and a system was developed for applying these techniques. Research in the experiment was carried out according to generally accepted methods.Results. The most significant increase in the onion crop was obtained on the variants of the complex application of the studied agricultural methods and amounted, on average, for 2011...2016 with an irrigation regime of 75...75...75% of HB on the standard variety Volgodonets – 159%, relative to the control, on a promising hybrid Octant F1 – 118%, on the hybrid – 125%. With the regime of 70...80...75% of HB on the Volgodonets standard grade – 155%, relative to control, on the promising Oktant F1 hybrid 113%, on the Valero F1 hybrid – 115%. When calculating the cultivation efficiency of this crop, economic data were obtained, the value of which allows us to conclude that when planning the growth of onion production efficiency, agricultural producers are recommended to introduce agricultural technology with a profitability of 253.63%: promising hybrid Octant F1, irrigation mode – differentiated, background N450P180K135+Mortar+Energy-M. Against this background, in the context of research on the variety and hybrids, the maximum return on production costs is 3.2 rubles. An analysis of data on a combination of crop-forming factors showed that for onions when cultivating promising hybrids Octant F1 and Valero F1, when planning yields of 130 and 150 t/ha, it is necessary to maintain a moisture level of 70...80...75% HB, and when grown without fertilizers and when planning 110 t/ha it is enough to create a permanent irrigation regime.